Topical Application of Ozonated Oils for the Treatment of MRSA Skin Infection in an Animal Model of Infected Ulcer - Vanessa Silva; Cecília Peirone; Rosa Capita; Carlos Alonso-Calleja; José A. Marques-Magallanes; Isabel Pires; Luís Maltez; José Eduardo Pereira; Gilberto Igrejas; Patrícia Poeta (Biology, 2021)
Diabetic foot ulcers are a common cause of morbidity in diabetic patients. One of the main pathogens found in these ulcers is methicillin-resistant Staphylococcus aureus (MRSA). MRSA often carries resistance to several classes of antibiotics and their infections are becoming harder to treat. Therefore, new alternatives are urgently needed. Thus, this study aimed to investigate the capacity of topical ozonated oil application on the treatment of early-stage skin infected with MRSA in an animal model. Ozonated oil was prepared from a mixture of oils subjected to a gas stream of O2/O3 mixture. Sixteen Wistar rats were inoculated by an intradermic injection of MRSA suspension, producing an abscess lesion. After 3 days, the skin epidermis was removed to open the wound. Group 1 received an application of oil mixture without ozone treatment and Group 2 received an application of ozonated oil. After the treatment period, skin was collected, colony-forming units (CFU) of bacteria were quantified and the histological analysis of the skin was carried out. Skin samples from the control 1 and 2 had a bacterial load was of 1.1 × 105 and 5.7 × 103 CFU/mL, respectively. Group 2 showed better wound healing from mild to moderate epidermal regeneration. Topical application of ozonated vegetable oil in MRSA-infected skin in rats showed a small reduction of the bacterial load and better wound healing.